One puzzling afternoon - Critchley, Emily, 1986- (Sourcebooks Landmark, 2023)
""An uplifting, bittersweet story with a page-turning mystery at its heart. Emily Critchley writes about aging and memory with huge warmth and compassion. A beautifully atmospheric and endearing book.'' --Freya Sampson, author of The Last Chance Library. For readers of Elizabeth is Missing with notes of The Maid comes a dual-timeline novel that balances heartfelt tenderness with a suspenseful mystery as elderly Edie Green uncovers the clues behind her best friend's disappearance before the truth is lost in her memory forever. I kept your secret Lucy. I've kept it for more than sixty years... It is 1951, and at number six Sycamore Street fifteen-year-old Edie Green is lonely. Living with her eccentric mother and her mother's new boyfriend, she is desperate for something to shake her from her dull, isolated life. So when the popular, pretty Lucy Theddle befriends Edie, she thinks all her troubles are over. Even though Lucy has a secret, one Edie is not certain she should keep. Then Lucy goes missing. Now in 2018, Edie is eighty-four and still living in the same small town, when one afternoon she glimpses Lucy Theddle, still looking the same as she did at fifteen. Her family write it off as one of her many mix ups, there's a lot Edie gets confused about these days. But Edie knows she's the key to finding Lucy. Time is running out and Edie must piece together the clues before Lucy is forgotten forever"--